Political corruption and capture of the minority1. (22nd July 2019) - Giannoccolo, Pierpaolo; Lisciandra, Maurizio
Abstract: This article presents a model of political corruption in which a briber can choose either to bribe only the incumbent party or to capture also the opposition party to sterilize its monitoring role. The analysis also explores interparty collusion, media independence, and political contestability. The model suggests that policies aiming to strengthen the role of minorities can produce ambiguous effects as they may induce bribers' avoidance behavior. Reputational sanctions appear to be less effective than criminal ones, although political contestability increases their deterrence effect. Paradoxically, harsh criminal sanctions may induce tacit collusion because minorities highly regard their outcomes once in power.